The Continuity of Islamization of Space and Architecture in Javanese Tomb and Masjid Makam - Yulia Pratiwi; Ibrahim Numan; Noor Cholis Idham (Department of Architecture Universitas Muhammadiyah Jakarta, 2023)
Research on Islamization of mosque at tomb complex (masjid makam) has not been found much. The aim is to examine the new meaning of Islam to differentiate from Hindu-Buddha in mosque architecture in Sunan Drajat’s tomb and masjid makam. This research used a semiotic analysis about the Islamization on architecture aspects. The conclusion is the continuity of Islamization in rituals is more dominated in the tomb of Sunan Drajat than in masjid makam. Barokah well has connotative meanings as a source of blessings and sustenance. Mustaka has the connotative meaning as a symbolization of one god. The seven terraces symbolize the seven tanazul or the creation of humans to a perfect level. The existence of the Sunan Drajat’s tomb and masjid makam had an impact on the settlements growth and creates a city image that Paciran Lamongan is a pondok pesantren city.